USE OF MULTIMEDIA TECHNOLOGIES IN FOREIGN LANGUAGE TEACHING - Зохидова, Севара; Xushvaqtova , Nigina (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
Nowadays, information technology has become an integral part of our life. It's almost impossible to find sphere now human activities, where some of the tasks would not be solved with the help computer and the Internet. Active use of information technology is also observed in education.